CO2‐Activated Reversible Transition between Polymersomes and Micelles with AIE Fluorescence. (24th June 2019) - Zhang, Dapeng; Fan, Yujiao; Chen, Hui; Trépout, Sylvain; Li, Min‐Hui
Abstract: Fluorescent polymersomes with both aggregation‐induced emission (AIE) and CO2 ‐responsive properties were developed from amphiphilic block copolymer PEG‐ b ‐P(DEAEMA‐ co ‐TPEMA) in which the hydrophobic block was a copolymer made of tetraphenylethene functionalized methacrylate (TPEMA) and 2‐(diethylamino)ethyl methacrylate (DEAEMA) with unspecified sequence arrangement. Four block copolymers with different DEAEMA/TPEMA and hydrophilic/hydrophobic ratios were synthesized, and bright AIE polymersomes were prepared by nanoprecipitation in THF/water and dioxane/water systems. Polymersomes of PEG45 ‐ b ‐P(DEAEMA36 ‐ co ‐TPEMA6 ) were chosen to study the CO2 ‐responsive property. Upon CO2 bubbling vesicles transformed to small spherical micelles, and upon Ar bubbling micelles returned to vesicles with the presence of a few intermediate morphologies. These polymersomes might have promising applications as sensors, nanoreactors, or controlled release systems. Abstract : AIE‐Polymersome aus dem CO2 ‐responsiven amphiphilen Blockcopolymer PEG‐ b ‐P(DEAEMA‐ co ‐TPEMA) zeigen einen reversiblen, CO2 ‐getriebenen Vesikel‐Micell‐Übergang. Beim Einleiten von CO2 gehen Vesikel in kleine, kugelförmige Micellen über, die danach wiederum Vesikel bilden, wenn Ar eingeleitet wird. AIE: aggregationsinduzierte Emission.